Diamine crossklinked anion exchange membranes based on poly(vinyl benzyl methylpyrrolidinium). (6th January 2021) - Li, Huanhuan; Dong, Jianhao; Cao, Xiaoru; Ren, Xiaorui; Hao, Zhe; Yang, Jingshuai
Abstract: Developing anion exchange membranes (AEMs) with high ionic conductivity, excellent chemical stability and superior alkaline resistance simultaneously is a remarkable challenge. In this work, a series of high-performance covalently crosslinked AEMs are successfully designed by tethering the flexible methylpyrrolidinium grafted poly (vinyl benzyl chloride) (PVBMPy) backbone and rigid polysulfone (PSF) backbone and employing N, N, N′, N′ -tetramethyl-1, 6-hexanediamine (TMHDA) as the crosslinker. The PVBMPy ionomer, as the anion conductor, exhibits remarkable alkali resistance while the existence of rigid PSF chain ensures sufficient mechanical strength. The properties of various membranes are optimized through adjusting the adding amount of TMHDA into the casting solution. The fabricated PVBMPy-CL- x %PSF membranes possess a superior oxidative stability against radicals attack, and simultaneously display enhanced dimensional and mechanical stabilities, acceptable conductivity and robust alkaline stability. As an example, the PVBMPy-CL-15%PSF membrane occupies a weight residual rate of 71.3% after immersing in the Fenton solution at 60 °C for 120 h, a volume swelling of 26.2%, a tensile stress at break of 13.1 MPa at room temperature and an ionic conductivity of 32.9 mS cm −1 at 80 °C, and maintains its initial ionic conductivity of 70.5% after exposure for 580 h in 1 M KOH at 80 °C. Graphical abstract: Image 1 Highlights: Pyrrolidinium PVBC with crosslinked diamine networks for anion exchange membranes. Membranes possess a superior oxidative stability toward the attack of radicals. Membranes exhibit good mechanical properties and alkali resistance simultaneously.